Analysis the Ability of Mathematic Connection With Cooperative Learning Model Thinking Pair Share and Thinking Pair Square - Jannah, Miftakhul; Paridjo, Paridjo; Utami, Wikan Budi (Study Program of Mathematics Education University of Muhammadiyah Malang, 2019)
The study aims to determine the better mathematical connection capabilities between those taught using cooperative learning models of the type of Think Pair Share or Think Pair Square, and describe the mathematical connection ability of students taught by cooperative learning models of Think Pair Share and Think Pair Square types. The population in this study were all students of class VIII of SMP Negeri 2 Adiwerna in the academic year of 2017/2018. Quantitative samples use 2 experimental classes. While the qualitative sample is 12 high, medium and low ability students. Data collection was carried out quantitatively, namely by tests, and qualitative by observation, documentation, and interviews. The results of this study showed that the mathematical connection ability taught with the Think Pair Share type of cooperative learning model was better than Think Pair Square, the mathematical connection ability of students taught by Think Pair Share and Think Pair Square learning models was partly achieved by the low group students , medium, and high.